Delivery of amphotericin B for effective treatment of Candida albicans induced dermal mycosis in rats via emulgel system: Formulation and evaluation - Aditya Ganeshpurkar; Pooja Vaishya; Sumeet Jain; Vikas Pandey; Divya Bansal; Nazneen Dubey (Wolters Kluwer Medknow Publications, 2014)
Background: Amphotericin B (AmB) is among the gold standard antifungal agents used for the treatment of the wide range of fungal infections. However, the drug has various side- effects. Transdermal approach for the delivery of drug is one of the accepted and convenient modes of drug delivery. Aim: The current work was designed to formulate and to evaluate the AmB emulgel system. Materials and Methods: In the preparation of AmB emulgel, Carbopol 930 was used as a gel in this study. The formulation was evaluated for viscosity, spreadability, drug content, drug release and in vitro and in vivo antifungal testing. Results: AmB emulgel was found to penetrate skin effectively and without any irritation. Further, in vivo studies revealed effective therapeutic potential against Candida albicans induced dermal mycosis. Conclusions: The current work, for the first time, revealed effective delivery of AmB across the skin.